RANCANG BANGUN SISTEM PENGAMANAN TRANSFUSI DARAH BERBASIS MIKROKONTROLER ATMega 8535 - Raja Embun Sari; Rizal Thalib (Prodi Teknik Elektromedik Universitas Sari Mutiara Indonesia, 2022)
Blood warmer is a tool that is used to warm blood in the process of blood transfusion. Inside the blood warmer there are several main parts that must be considered, in the main part that must be considered is the blood fluid detector section. With the main purpose so that blood does not rise again fill the blood bag. The design of this tool aims to get the design of a security system for blood transfusion by using a photodiode detector as an indicator of blood flow that will be displayed in the form of sound. This research starts from the stages of collecting various sources, gathering information, designing tool products, designing and performing function tests. The hardware includes the design of the power supply circuit, the minimum system circuit of the ATMega8535 microcontroller, the liquid blood detector circuit, the buzzer circuit, and the servo motor circuit. While the design for software includes basic complier language programming. The working principle of the overall system is: The photodiode detector circuit will provide input to the microcontroller to be processed and produce output in the form of buzzer and servo motor closing the hose